Salt-dependent chemotaxis of macrophages - Mueller, Silke; Quast, Thomas; Schröder, Agnes; Hucke, Stephanie; Klotz, Luisa; Jantsch, Jonathan; Gerzer, Rupert; Hemmersbach, Ruth; Kolanus, Waldemar (PLoS ONE, 2013)
Besides their role in immune system host defense, there is growing evidence that macrophages may also be important regulators of salt homeostasis and blood pressure by a TonEBP-VEGF-C dependent buffering mechanism. As macrophages are known to accumulate in the skin of rats fed under high salt diet conditions and are pivotal for removal of high salt storage, the question arose how macrophages sense sites of high sodium storage. Interestingly, we observed that macrophage-like RAW264.7 cells, murine bone marrow-derived macrophages and peritoneal macrophages recognize NaCl hypertonicity as a chemotactic stimulus and migrate in the direction of excess salt concentration by using an in vitro transwell migration assay. While RAW264.7 cells migrated toward NaCl in a dose-dependent fashion, no migratory response toward isotonic or hypotonic media controls, or other osmo-active agents, e.g. urea or mannitol, could be detected. Interestingly, we could not establish a specific role of the osmoprotective transcription factor TonEBP in regulating salt-dependent chemotaxis, since the specific migration of bone marrow-derived macrophages following RNAi of TonEBP toward NaCl was not altered. Although the underlying mechanism remains unidentified, these data point to a thus far unappreciated role for NaCl-dependent chemotaxis of macrophages in the clearance of excess salt, and suggest the existence of novel NaCl sensor/effector circuits, which are independent of the TonEBP system.
EVALuna2:7634